Welfare trends in Romania, 1990-2014 - Şerban Toader; Victor Iancu; Dan Olteanu (Romanian Academy, National Institute for Economic Research, 2016)
We aim to clarify how objective wellbeing in Romania, as expressed by statistical indicators, evolved during two and a half decades (1990-2014). We considered three main pillars of welfare - health, income & consumption, education - and we investigated their evolution for five CEE countries: Romania, Bulgaria, the Czech Republic, Hungary and Poland, to which we added a western european country - Germany -, as a banchmark for comparison. We conclude that Romania's welfare development, determined using our indicators and methodology, appears to be consistent and robust. Considering the overall welfare development relative scores, Romania ranks second among the countries under survey, after Poland. Accordingly, even though for some indicators Romania was and still is positioned below other CEE countries in absolute figures, the positive evolutions we have observed for some indicators show a convergence tendency with countries better positioned so far, as confirmed by reducing gaps for these indicators. However, this 2nd rank comprises mixed performances among the analysed indicators. For instance, Romania's wellbeing development lags behind some other CEE countries for life expectancy, tertiary enrolment and human capital. As a result, absolute gaps have expanded. Moreover, in the case of GDP, although its relative growth was lower only than that of Poland, the absolute gap between Romania and other two countries (Czech Republic and Germany) widened in 2014, as compared with 1991. This study has been financed by KPMG Romania.
Keywords: D60; I31; I10; E01; E21; I20; 330; wellbeing; health; income; consumption; education; CEE